Sodium-ion battery electrolyte, preparation method thereof and sodium-ion battery

By combining strong and weak solvents to form a multi-component inorganic CEI layer, the problem of unstable positive electrode electrolyte interface in sodium metal batteries is solved, the ionic conductivity and cycle stability of sodium-ion batteries are improved, and the battery life is extended.

CN121238022APending Publication Date: 2025-12-30BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511217892.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-12-30

AI Technical Summary

Technical Problem

In existing sodium metal batteries, the positive electrode electrolyte interface is unstable, leading to disordered growth of sodium dendrites, electrolyte consumption, and irreversible loss of active materials. Furthermore, traditional electrolyte designs suffer from problems such as poor wettability, high cost, and poor sodium salt dissociation ability.

Method used

By using a combination of strong and weak solvents, the solvation shell structure of Na+ is controlled to form a multi-component inorganic CEI layer, which blocks the contact between the solvent and the positive electrode active material, avoids solvent oxidation and decomposition, and optimizes the element ratio through machine learning to form a highly stable interface.

Benefits of technology

It improves the ionic conductivity and Na+ diffusion activation energy of sodium-ion batteries, enhances the cycle stability and capacity retention of the batteries, prevents electrode structure collapse, and extends battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121238022A_ABST
    Figure CN121238022A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium-ion battery electrolyte, a preparation method thereof and a sodium-ion battery. The electrolyte comprises a solvent including a strong solvent and a weak solvent, the strong solvent is selected from one or two of trimethyl phosphate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and tetrahydrofuran, and the weak solvent is selected from one or two of 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether, bis (2, 2, 2-trifluoroethyl) ether and diethyl carbonate; the solute is dissolved in the solvent and comprises a first solute and a second solute, the first solute comprises at least one of sodium hexafluorophosphate, sodium perchlorate and sodium bis (fluorosulfonyl) imide, the second solute comprises at least one of sodium nitrate, sodium difluoro (oxalato) borate and sodium tetrafluoroborate, the concentration of the first solute is 1.0-2.0 mol / L, and the concentration of the second solute is 0.01-0.1 mol / L. According to the sodium ion battery prepared from the electrolyte provided by the invention, side reaction between an electrode and the electrolyte is prevented, and continuous consumption of the electrolyte and thickening of a CEI layer are prevented, so that the electrode structure is stabilized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of sodium ion batteries, in particular, to a sodium ion battery electrolyte, a preparation method thereof and a sodium ion battery. BACKGROUND

[0002] Sodium metal batteries (SMBs) have become a promising energy storage system due to the abundant resource of sodium and the similar physicochemical properties to lithium metal. However, its industrialization is limited by two major technical challenges: one is the unstable positive electrode electrolyte interface, and the other is the thermal runaway caused by the reaction of metal sodium and flammable electrolyte. In the traditional electrolyte, the formation of the positive electrode electrolyte interface is a self-limiting reaction, which will lead to the disorderly growth of sodium dendrites, the continuous consumption of electrolyte and the irreversible loss of active materials, and the sodium dendrites may also pierce the separator to cause internal short circuit.

[0003] To solve these problems, the prior art adopts strategies such as adding additives, electrolyte design, and interface modification. Among them, high-concentration electrolyte, local high-concentration electrolyte and weakly solvated electrolyte are the main electrolyte design strategies. However, high-concentration electrolyte has the problems of poor wettability and high cost; the diluent used in local high-concentration electrolyte is expensive and has poor sodium salt dissociation ability, hindering the migration of sodium ions; weakly solvated electrolyte may lead to insufficient salt solubility and reduced cation conductivity, causing battery capacity attenuation.

[0004] The content of the background section merely represents the applicant's knowledge and does not mean the prior art in the field. SUMMARY

[0005] In view of the deficiencies of the prior art, the present application provides a sodium ion battery electrolyte, a preparation method thereof and a sodium ion battery.

[0006] The sodium ion battery electrolyte provided by the present application comprises:

[0007] a solvent, including a strong solvent and a weak solvent, the strong solvent being selected from one or two of trimethyl phosphate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and tetrahydrofuran, and the weak solvent being selected from one or two of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether and diethyl carbonate; and

[0008] a solute dissolved in the solvent, including a first solute and a second solute, the first solute including at least one of sodium hexafluorophosphate, sodium perchlorate and sodium bisfluorosulfonylimide, and the second solute including at least one of sodium nitrate, sodium difluoro oxalate borate and sodium tetrafluoroborate, the concentration of the first solute being 1.0-2.0 mol / L, and the concentration of the second solute being 0.01-0.1 mol / L.

[0009] In some embodiments of the present application, the concentration of the first solute is 1.3-1.5 mol / L, and the concentration of the second solute is 0.04-0.08 mol / L.

[0010] In some embodiments of the present application, the molar ratio of the first solute to the second solute is (1.3-1.5):(0.04-0.08).

[0011] In some embodiments of the present application, the volume ratio of the strong solvent to the weak solvent is (0.5-1.5):(0.05-0.1).

[0012] In some embodiments of the present application, the first solute is sodium hexafluorophosphate, the second solute is sodium nitrate, the strong solvent is trimethyl phosphate, and the weak solvent is diethyl carbonate.

[0013] In some embodiments of the present application, the molar ratio of sodium hexafluorophosphate to sodium nitrate is 1.445:0.069, and the volume ratio of trimethyl phosphate to diethyl carbonate is 0.928:0.072.

[0014] The method for preparing the sodium-ion battery electrolyte provided by the present application comprises:

[0015] removing water in the solute and the solvent;

[0016] preparing the strong-weak solvent mixture from the strong solvent and the weak solvent; and

[0017] dissolving the solute in the strong-weak solvent mixture.

[0018] In some embodiments of the present application, the sodium-ion battery further comprises a positive electrode, and after the sodium-ion battery is cycled, a transition layer and an inorganic CEI layer on the transition layer are formed on the surface of the positive electrode, the transition layer comprises NaF and fluorine / phosphorus organic oligomers, and the inorganic CEI layer comprises NaF, Na3PO4, and NaN x O y .

[0019] In some embodiments of the present application, the capacity retention rate of the sodium-ion battery after 300 cycles is greater than 87%.

[0020] The present application utilizes the difference in the solvation ability between the strong solvent and the weak solvent to regulate the solvation shell structure of Na + , and in the process of battery operation, the multi-component inorganic CEI layer can be formed by preferential decomposition of the double sodium salt, and a small amount of decomposition of the strong solvent and the weak solvent in the later stage can supplement the organic components, thereby avoiding the over-thickness or looseness of the inorganic CEI layer.

[0021] The electrolyte provided in this application can increase the degree of solute dissociation, reduce the proportion of ionic aggregates (AGGs), and increase ionic conductivity, Na + The diffusion activation energy is reduced, thereby improving the performance of sodium-ion batteries.

[0022] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0023] Figure 1 This is a process flow diagram for preparing sodium-ion battery electrolyte according to an embodiment of this application.

[0024] Figure 2 This is a schematic diagram illustrating the cycle stability of sodium-ion batteries assembled with electrolytes prepared in Examples 1 and 1-3 of this application.

[0025] Figure 3 This is a comparison of the cycle stability of Na||Na symmetric batteries assembled with electrolytes prepared in Examples 1 and 1-3 of this application.

[0026] Figure 4 High-resolution images of the positive electrode surface of sodium-ion batteries assembled with electrolytes prepared in Examples 1, 2, and 3 of this application after cycling.

[0027] Figure 5 This is a depth analysis diagram of the positive electrode surface of a sodium-ion battery assembled with the electrolytes prepared in Example 1 and Comparative Example 2 of this application after 50 cycles.

[0028] Figure 6 Normalized XPS fitting curves of C1s, F1s and N1s peaks on the positive electrode surface of a sodium-ion battery assembled with the electrolyte prepared in Example 1 of this application after 50 cycles. Detailed Implementation

[0029] The specific embodiments of the present invention will be described in more detail below with reference to the accompanying drawings and examples, so as to better understand the solution of the present invention and its advantages in various aspects. However, the specific embodiments and examples described below are for illustrative purposes only and are not intended to limit the present invention.

[0030] It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments, and those skilled in the art will readily be able to modify or appropriately alter and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to implement and apply the technology of this invention.

[0031] The sodium-ion battery electrolyte (hereinafter referred to as electrolyte) provided in the present application comprises a solute and a solvent. The solute comprises a first solute and a second solute. The first solute comprises at least one of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), and sodium bisfluorosulfonylimide (NaFSI), and the second solute comprises at least one of sodium nitrate (NaNO3), sodium difluoro(oxalato)borate (NaDFOB), and sodium tetrafluoroborate (NaBF4). The solvent comprises a strong solvent and a weak solvent, the strong solvent is selected from one or two of trimethyl phosphate (TMP), ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (G2), and tetrahydrofuran (THF), and the weak solvent is selected from one or two of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), bis(2,2,2-trifluoroethyl) ether (BTFE), and diethyl carbonate (DEC).

[0032] In the working process of the battery, the at least two sodium salts and the strong and weak solvents synergistically act, the sodium salts are preferentially decomposed to form an inorganic CEI layer, and the strong and weak solvents are slowly decomposed in the later stage to form a transition layer containing a small amount of organic components, and the transition layer is located between the inorganic CEI layer and the positive active material. For example, when the solute is NaPF6 and NaNO3, the strong solvent is TMP, and the weak solvent is DEC, after the sodium-ion battery is cycled, an inorganic CEI layer is formed on the surface of the positive electrode, and at this time the inorganic CEI layer comprises NaF, Na3PO4, and NaN x O y (x>0, y>0).

[0033] The inorganic CEI layer has high chemical stability and can form a dense physical barrier to directly block the contact of solvent molecules with the positive active material, thereby avoiding the continuous oxidative decomposition of the solvent at high voltage. The inorganic CEI layer can block the dissolution of transition metal ions of the positive electrode material (for example, Ni, Mn, Fe of NaNi 0.33 Mn 0.33 Fe 0.33 O2) by chemical adsorption or physical isolation, thereby avoiding the collapse of the electrode structure.

[0034] The present application utilizes the difference in solvation ability between the strong solvent and the weak solvent to regulate the solvation shell structure of Na + In the working process of the battery, it can ensure that the double sodium salt is preferentially decomposed to form a multi-component inorganic CEI layer, and the strong and weak solvents are decomposed in the later stage to supplement a small amount of organic components, thereby avoiding the over-thickness or looseness of the inorganic CEI layer.

[0035] The electrolyte provided in the present application can improve the dissociation degree of the solute, reduce the proportion of ion aggregates (AGGs), increase the ionic conductivity, and reduce the diffusion activation energy of Na + , thereby improving the performance of the sodium-ion battery.

[0036] The concentration of the first solute is 1.0-2.0 mol / L. At this concentration, it is more conducive to generate inorganic CEI layer and transition layer. In some embodiments of the present application, the concentration of the first solute can be 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L or 1.745 mol / L. Further optionally, the concentration of the first solute is 1.3-1.5 mol / L.

[0037] The concentration of the second solute is 0.01-0.1 mol / L. At this concentration, it is more conducive to generate inorganic CEI layer and transition layer. In some embodiments of the present application, the concentration of the second solute can be 0.01 mol / L, 0.03 mol / L, 0.05 mol / L, 0.07 mol / L, 0.08 mol / L or 0.1 mol / L. Further optionally, the concentration of the second solute is 0.04-0.08 mol / L.

[0038] The molar ratio of the first solute and the second solute is (1.0-2.0):(0.01-0.1). In some embodiments of the present application, the molar ratio of the two components in the solute can be 1.0:0.01, 1.0:0.1, 2.0:0.01, 2.0:0.1. Further optionally, the molar ratio of the first solute and the second solute is (1.3-1.5):(0.04-0.08), for example 1.3:0.04, 1.5:0.04, 1.3:0.08, 1.5:0.08.

[0039] Optionally, the volume ratio of the strong solvent and the weak solvent is (0.5-1.5):(0.05-0.1). The strong solvent is more than the weak solvent. In some embodiments of the present application, the volume ratio of the strong solvent and the weak solvent can be 0.5:0.05, 0.5:0.1, 1.5:0.05 or 1.5:0.1.

[0040] In some embodiments of the present application, when the first solute is NaPF6, the second solute is NaNO3, the strong solvent is TMP and the weak solvent is DEC, the molar ratio of NaPF6 and NaNO3 can be 1.445:0.069, and the volume ratio of TMP and DEC can be 0.928:0.072. For example, the amount of NaPF6 and NaNO3 is 1.445 mmol and 0.069 mmol respectively, and the amount of TMP and DEC is 0.928 L and 0.072 L respectively. The applicant found that the performance of the sodium ion battery is best at this time.

[0041] The present application further provides a method for preparing an electrolyte of a sodium ion battery. As shown in Figure 1 S1-S3 steps.

[0042] S1: Removes water from the solute and solvent.

[0043] Optionally, the solute is dried in a vacuum oven (e.g., at 50°C for 24 hours). Optionally, the solvent is dried with molecular sieves (e.g., for 3 days).

[0044] S2: Prepare a mixture of strong and weak solvents.

[0045] The strong solvent and the weak solvent are mixed and stirred until a clear solution is obtained, then the mixing is stopped to obtain a mixture of strong and weak solvents.

[0046] S3: Dissolve the solute in a mixture of strong and weak solvents.

[0047] The solute is added to a mixture of strong and weak solvents and stirred until a clear solution is obtained, which is the electrolyte.

[0048] This application also provides a sodium-ion battery, including the above-mentioned electrolyte. The sodium-ion battery further includes a positive electrode and a negative electrode. After cycling, the sodium-ion battery provided in this application forms a transition layer and an inorganic CEI layer on the surface of the positive electrode. When the solute is NaPF6 or NaNO3, the strong solvent is TMP, and the weak solvent is DEC, the transition layer includes NaF and fluorine / phosphorus organic oligomers, and the inorganic CEI layer includes NaF, Na3PO4, and NaN. x O y Optionally, the sodium-ion battery retains more than 87% of its capacity after 300 cycles.

[0049] In traditional electrolytes, the formation of the positive electrode-electrolyte interface is a non-self-limiting reaction, leading to continuous electrolyte consumption and irreversible loss of active materials, which in turn causes capacity decay. The sodium-ion battery provided in this application forms an inorganic CEI layer after cycling, effectively isolating the electrode from the electrolyte, preventing side reactions between them, and preventing continuous electrolyte consumption and CEI layer thickening. This stabilizes the electrode structure and avoids battery performance degradation caused by side reactions.

[0050] One embodiment of this application uses machine learning to optimize the electrolyte for sodium-ion batteries.

[0051] An interactive, physically-based ensemble method using a Bayesian optimization framework assists in controlling elemental ratios to create interface defects and improve discharge specific capacity. This method iteratively reverse-engineers a high-stability sodium-ion battery. In each iteration, a modular ensemble design leverages the advantages of multiple machine learning models to predict specific capacity. Simultaneously, the interactive mode guides the selection and training of machine learning models based on prior physical knowledge in the sodium-ion battery field, ultimately accelerating optimization.

[0052] Specifically, the following steps are included:

[0053] Step 1: Mathematical abstraction.

[0054] To adapt to machine learning models, the original material optimization problem can be mathematically abstracted into a function optimization problem. In this embodiment, the first solute is sodium hexafluorophosphate, the second solute is sodium nitrate, the strong solvent is diethyl phosphate, and the weak solvent is trimethyl phosphate. Their molar amounts and volumes can be regarded as the independent variables of a function: x1 (molar amount of sodium hexafluorophosphate), x2 (molar amount of sodium nitrate), x3 (volume of diethyl phosphate), and x4 (volume of trimethyl phosphate) (x3 + x4 = 1). The relaxation voltage difference of the battery can be regarded as the dependent variable of a function: y1, and the discharge specific capacity of the battery after stabilization can be regarded as the dependent variable: y2. Therefore, the integrated method provided by this invention only needs to adjust x1, x2, and x3 to make y1 as small as possible and y2 as large as possible to achieve the reverse design of a highly stable sodium-ion battery.

[0055] Step 2: Provide initial data.

[0056] The initial raw material dosages can be randomly assigned, and there are no requirements for the amount of data; generally, 2-10 sets are sufficient to roughly estimate the relaxation voltage and discharge specific capacity. Sodium hexafluorophosphate (NaPF6) and sodium nitrate (NaNO3) were dried in a vacuum oven at 50°C for 24 hours, while trimethyl phosphate (TMP) and diethyl carbonate (DEC) were dried using molecular sieves for 3 days. NaPF6, NaNO3, TMP, and DEC were weighed and stirred for 3 hours to obtain a clear solution. The entire preparation process was carried out in an argon-filled glove box. The prepared electrolyte was used to assemble a battery for electrochemical testing. The voltage difference between the first and third cycles was taken as y1, and the discharge specific capacity of the third cycle was taken as y2, which were then used as inputs into a machine learning model for optimal ratio prediction.

[0057] Step 3: Machine learning to predict material properties.

[0058] We choose a machine learning prediction model to predict unknown components based on existing data. Since our available data is limited and insufficient to support accurate predictions by most traditional machine learning models, we generally choose a probabilistic Gaussian process regression (GPR) model. This model predicts material properties while also quantitatively providing the uncertainty of the prediction. This quantitative uncertainty output can efficiently guide us in selecting recommended experimental points in the next step. Therefore, if we choose traditional machine learning prediction models, such as random forests (RF), support vector machines (SVM), or fully connected neural networks (FNN), they cannot directly output uncertainty results like GPR; they can only provide a prediction of material properties. We also need to perform Monte Carlo sampling to obtain quantitative uncertainty results.

[0059] Step 4: Define the acquisition function to recommend experimental components.

[0060] Considering that the accuracy of predictions decreases with limited data, it's not feasible to directly select the component with the best prediction performance for recommendation. Here, by balancing the prediction results and their uncertainty, two recommendation strategies are derived: "utilization" and "exploration." "Utilization" prioritizes recommending components with better predictions to optimize material properties; "exploration," on the other hand, prioritizes recommending components with greater uncertainty, selecting less accurate predictions for validation, which is more conducive to improving model prediction accuracy. To quantify this trade-off process, we can define an acquisition function, such as the simplest LCB, which uses linear weighting coefficients for the trade-off; more complex functions like MPI or EI, which use nonlinear weighting functions, can also be chosen. The final recommended experimental components are then selected based on this acquisition function.

[0061] Step 5: Experimentally measure the performance of the recommended components, update the dataset, and iterate through steps 2 through 5 until the target performance of the material meets the requirements.

[0062] In the specific experimental process, the prediction model and the acquisition function do not have to be fixed. The above iterative process can be carried out interactively based on the experimental results and physical experience in related fields.

[0063] Step 6: After three iterations, as shown in Table 1, the optimal ratio was determined by synthesizing only 14 samples: 1.445 mmol NaPF6, 0.069 mmol NaNO3, 0.928 mL TMP, and 0.072 mL DEC.

[0064] Step 7: Prepare cathode materials without NaNO3 and DEC elements for comparison. The difference between the synthesis process and Step 2 is that there is no NaNO3 or DEC. The contents of other solvents and solutes are the optimal values ​​predicted by machine learning. The preparation process and preparation conditions are the same as in Step 2.

[0065] Step 8: To better compare the electrochemical performance, an electrolyte outside the optimal solute-solvent ratio range was synthesized. The amounts of NaPF6 were 0.7 mmol, NaNO3 was 0.005 mmol, DEC was 0.3 mL, and TMP was 0.7 mL.

[0066] Table 1

[0067]

[0068] The present invention will now be described with reference to specific embodiments. The process conditions described in the following embodiments are exemplary, and their possible ranges are as shown in the foregoing description of the invention. For process parameters not specifically noted, conventional techniques can be used. The detection methods used in the following embodiments are all conventional detection methods in the industry. Unless otherwise specified, the reagents and instruments used in the technical solutions provided by the present invention can all be purchased from conventional channels or the market.

[0069] Example 1

[0070] (1) Sodium hexafluorophosphate (NaPF6) and sodium nitrate (NaNO3) were dried in a vacuum oven at 50°C for 24 hours, and trimethyl phosphate (TMP) and diethyl carbonate (DEC) were dried using molecular sieves for 3 days. 1.445 mmol of NaPF6 and 0.069 mmol of NaNO3 were weighed for use.

[0071] (2) A strong-weak solvent pair was formed by mixing strongly solvated trimethyl phosphate (TMP, ESPmin = -1.86 eV) and weakly solvated diethyl carbonate (DEC, ESPmin = -1.52 eV), with 0.928 mL of TMP and 0.072 mL of DEC. After stirring for 3 hours, a clear solution was obtained. 1.445 mmol of NaPF6 and 0.069 mmol of NaNO3 were added to the solvent, and stirring was continued for 3 hours to obtain a clear solution, labeled DHSE. All preparation processes were carried out in an argon-filled glove box.

[0072] Comparative Example 1

[0073] The difference between this comparative example and Example 1 is that:

[0074] The dosage of NaPF6 is 0.7 mmol, the dosage of NaNO3 is 0.005 mmol, the dosage of DEC is 0.3 mL, and the dosage of TMP is 0.7 mL.

[0075] Comparative Example 2

[0076] The difference between this comparative example and Example 1 lies in the electrolyte:

[0077] An electrolyte was prepared by dissolving 1.445 mmol of sodium hexafluorophosphate (NaPF6) in 0.072 mL of diethyl carbonate (DEC) and 0.928 mL of trimethyl phosphate (TMP) (labeled FDT).

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 1 lies in the electrolyte:

[0080] Dissolve 1.445 mmol of sodium hexafluorophosphate (NaPF6) in 1 ml of trimethyl phosphate (TMP) (labeled as FT).

[0081] Test case

[0082] Battery cycle stability testing methods: For sodium-ion batteries, the positive electrode material used is commercially available NaNi. 0.33 Mn 0.33 Fe 0.33 O2 was used, and a commercially available 14mm diameter sodium sheet was used as the negative electrode. First, coin cells were assembled in a glove box using the positive electrode, negative electrode, glass fiber separator, and electrolyte prepared according to the examples or comparative examples. The assembled cells were allowed to stand for 8 hours. After standing, cyclic testing was performed at 0.1C and a voltage range of 2–4.5V. For the Na||Na symmetric cell, both electrodes were sodium sheets, assembled in a glove box, using the examples or comparative examples as the electrolyte. After assembly, the symmetric cell was first allowed to stand for 4 hours, and then cyclically tested at 0.1mA cm⁻¹. 2- Activation was performed by constant current charge-discharge cycles at the current density for 5 cycles, with a single-step time of 2 hours, followed by activation at 0.2 mA cm⁻¹. 2- The constant current charge and discharge cycle was performed at the current density, with a single step time of 1 hour.

[0083] The surface of the electrode sheet after 50 cycles was analyzed using a transmission electron microscope (TEM, JEOL JEM-2100F).

[0084] The elemental composition and chemical composition of the samples were semi-quantitatively analyzed using X-ray photoelectron spectroscopy (ESCALAB MKII). The HOMO and LUMO energy levels of individual and multiple solvent molecules were calculated using Gaussian to analyze the oxidative decomposition of the electrolytes.

[0085] Time-of-flight secondary ion mass spectrometry (TOF-SIMS 5iontof) was used to perform in-depth analysis and three-dimensional visualization of the cathode materials of the cycled use examples and Comparative Example 1 to understand the composition and component distribution of CEI.

[0086] Figure 2 This diagram illustrates the cycle stability of sodium-ion batteries assembled with the electrolytes prepared in Examples 1 and 1-3 of this application. Figure 2 As can be seen, the sodium-ion battery assembled with the electrolyte provided in this application has a capacity retention rate of 87.5% after 300 cycles, while the sodium-ion battery assembled with the electrolyte in Comparative Example 1 has a capacity retention rate of only 32.1% after 200 cycles. Comparative Example 2 has a capacity retention rate of 82.3%, while Comparative Example 3 has a capacity retention rate of only 52.1% after 230 cycles.

[0087] Figure 3 This comparison examines the cycle stability of Na||Na symmetric batteries assembled with the electrolytes prepared in Examples 1 and 1-3 of this application. Figure 3 It can be seen that the electrolyte in the Na||Na symmetric battery assembled using the electrolyte prepared in Comparative Example 1 decomposed after less than 200 hours of cycling, and the electrolyte in the Na||Na symmetric battery assembled using the electrolytes prepared in Comparative Examples 2 and 3 decomposed after less than 400 hours of cycling.

[0088] Figure 4 High-resolution images of the positive electrode surface of sodium-ion batteries assembled with the electrolytes prepared in Examples 1, 2, and 3 of this application after cycling. Figure 4 As can be seen, after 30 cycles, the sodium-ion battery assembled with the electrolyte provided in this application shows the presence of the inorganic phase NaF on the positive electrode surface, and the CEI layer is relatively thin, with a transition layer existing between the CEI layer and the positive electrode active material particles. In Comparative Example 2, the sodium-ion battery assembled with the electrolyte shows the presence of the inorganic phase Na3P on the positive electrode surface after 30 cycles, but the CEI layer is thicker. No inorganic phase was observed on the positive electrode surface of the sodium-ion battery assembled with the electrolyte of Comparative Example 3 after 50 cycles.

[0089] Figure 5 This is a depth analysis image of the positive electrode surface of a sodium-ion battery assembled with the electrolytes prepared in Example 1 and Comparative Example 2 of this application after 50 cycles. Figure 5 As can be seen from the above, the surface of the positive electrode material of the sodium-ion battery prepared with the electrolyte provided in this application has a large amount of inorganic component NaF2 uniformly distributed. - POF2 - and prevent transition metals 58 Ni -The electrolyte provided in Comparative Example 2 resulted in the dissolution of the positive electrode material, which was coated with a large amount of organic components (C₂H₂O). - Meanwhile, the inorganic component NaF2 - POF2 - Unevenly distributed on the sample surface, accompanied by transition metals. 58 Ni - Dissolution.

[0090] Figure 6 Normalized XPS fitting curves of the C1s, F1s, and N1s peaks on the positive electrode surface of a sodium-ion battery assembled with the electrolyte prepared in Example 1 of this application after 50 cycles. Figure 6 Na3PO4, NaF, and NaN were observed in the P 2p, F 1s, and N 1s spectra. x O y The presence of inorganic compounds helps form a dense interface layer, effectively suppressing the dissolution of transition metals between the cathode and electrolyte under high voltage and electrolyte consumption.

[0091] Table 2 shows the calculated HOMO and LUMO energy levels of the solvation structure of the electrolyte prepared in Example 1 of this application. By calculating the HOMO energy level, it can be found that Na… + -PF6 - -TMP-NO3 - The highest HOMO energy level indicates that the combination of NaPF6 and NaNO3 salts can preferentially decompose into an inorganic CEI layer.

[0092] Table 2

[0093]

[0094] In summary, it can be seen that the sodium-ion battery prepared with the electrolyte provided in this application will form an inorganic CEI layer after cycling, which can effectively isolate the electrode from the electrolyte, prevent side reactions between the electrode and the electrolyte, prevent the continuous consumption of electrolyte and the thickening of the CEI layer, thereby stabilizing the electrode structure and avoiding the decline in battery performance caused by side reactions.

[0095] Obviously, the above embodiments are merely examples for clearly illustrating the present invention and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A sodium-ion battery electrolyte, characterized in that, The sodium-ion battery electrolyte comprises: a solvent, including a strong solvent and a weak solvent, the strong solvent being selected from one or two of trimethyl phosphate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and tetrahydrofuran, and the weak solvent being selected from one or two of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether and diethyl carbonate; and a solute dissolved in the solvent, including a first solute and a second solute, the first solute including at least one of sodium hexafluorophosphate, sodium perchlorate and sodium bisfluorosulfonylimide, and the second solute including at least one of sodium nitrate, sodium difluorooxalate borate and sodium tetrafluoroborate, the concentration of the first solute being 1.0-2.0 mol / L, and the concentration of the second solute being 0.01-0.1 mol / L.

2. The sodium-ion battery electrolyte of claim 1, wherein, The concentration of the first solute is 1.3-1.5 mol / L, and the concentration of the second solute is 0.04-0.08 mol / L.

3. The sodium-ion battery electrolyte of claim 1, wherein, The molar ratio of the first solute to the second solute is (1.3-1.5):(0.04-0.08).

4. The sodium-ion battery electrolyte of claim 1, wherein, The volume ratio of the strong solvent to the weak solvent is (0.5-1.5):(0.05-0.1).

5. The sodium-ion battery electrolyte of claim 1, wherein, The first solute is sodium hexafluorophosphate, the second solute is sodium nitrate, the strong solvent is trimethyl phosphate, and the weak solvent is diethyl carbonate.

6. The sodium-ion battery electrolyte of claim 5, wherein, The molar ratio of sodium hexafluorophosphate to sodium nitrate is 1.445:0.069, and the volume ratio of trimethyl phosphate to diethyl carbonate is 0.928:0.

072.

7. A method of preparing the sodium-ion battery electrolyte of any one of claims 1 to 6, characterized in that, The sodium-ion battery electrolyte comprises: removing water from the solute and the solvent; preparing the strong solvent and the weak solvent into a strong-weak solvent mixture; and dissolving the solute in the strong-weak solvent mixture.

8. A sodium-ion battery, characterized in that, The sodium-ion battery electrolyte comprises:

9. The sodium-ion battery of claim 8, wherein, The sodium-ion battery further comprises a positive electrode, after being cycled, a transition layer and an inorganic CEI layer on the transition layer are formed on the surface of the positive electrode, the transition layer comprises NaF and fluorine / phosphorus organic oligomers, the inorganic CEI layer comprises NaF, Na3PO4 and NaN x O y .

10. The sodium-ion battery of claim 8, wherein, The capacity retention rate of the sodium-ion battery after 300 cycles is greater than 87%.